Silicone Plate for the Prevention of Postoperative Adhesions in Patients with Asherman Syndrome - Maho Miyagi; Keiko Mekaru; Sugiko Oishi; Chiaki Urasoe; Kozue Akamine; Yoichi Aoki (Case Reports in Obstetrics and Gynecology)
Purpose. Re-adhesion rates following hysteroscopic adhesiolysis have remained high. Accordingly, we present a case involving temporary placement of an intrauterine silicone plate to prevent re-adhesions following hysteroscopic adhesiolysis in a 36-year-old woman with Asherman syndrome. Methods. After hysteroscopic adhesiolysis, a silicone plate molded to the uterine cavity’s shape was inserted into the uterine cavity and left in place for 1 month. Results. The patient had a history of endometrial curettage for endometrial polyps. After the procedure, she developed amenorrhea and experienced infertility for 5 years despite four cycles of in vitro fertilization and embryo transfer. Following admission to our hospital, hysteroscopic examination showed a wide area of intrauterine adhesions for which hysteroscopic adhesiolysis and silicone plate insertion were performed. The silicone plate was removed after 1 month. No intrauterine adhesions were observed during the subsequent hysteroscopic examination. After a thawed embryo transfer, the patient became pregnant and delivered a healthy baby. Conclusions. A silicon plate may be considered a useful tool for preventing re-adhesion following hysteroscopic adhesiolysis without serious complications.